ISLAMIC INHERITANCE LAW IN SARUASO AND SAWAH TANGAH VILLAGES BASED ON ISLAMIC PRINCIPLES - Rajab, Rajab; Elizamiharti, Elizamiharti; Muslim, Muslim (Islam Futura, 2022)
This research aims to comprehend the practice of dividing the inheritance in Saruaso and Sawah Tangah Villages following the distribution principle of inheritance law distribution in Islam. The problem was that there were different views on the distribution of inheritance in the Saruaso and Sawah Tangah Villages with the provisions on the distribution of inheritance based on Islamic teachings. Meanwhile, the people of Saruaso and Sawah Tangah Villages embraced Islam. This research used a survey method. The research object was Niniak Mamak (indigenous stakeholders) and Bundo Kanduang (village's mothers) in two villages, Kanagarian Saruaso and Kanagarian Sawah Tangah. The sampling technique used was the purposive sampling technique. The results of this research are the practice of dividing inheritance in Saruaso and Sawah Tangah Village; in this case, low inheritance does not conflict with the provisions that apply to inheritance law in Islamic teachings (based on Faraid law). While the division of high inheritance follows customary provisions, this is because the high inheritance belongs to the people (tribes), cannot be traded, and cannot be divided individually.